2016
DOI: 10.1007/s10157-016-1300-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of vitamin D analogs is independently associated with the favorable renal prognosis in chronic kidney disease stages 4–5: the CKD-ROUTE study

Abstract: The use of vitamin D analogs is independently associated with the preservation of renal function in patients with pre-dialysis CKD stages 4-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Only in KTRs not receiving active vitamin D, low 1,25D levels were associated with poor outcome. To date, a small observational study among KTRs 29 , as well as a propensity-matched study of CKD 30 , suggests that active vitamin D therapy improves renal outcomes. Future randomized interventional studies are therefore warranted to assess the effect of active vitamin D use on graft outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Only in KTRs not receiving active vitamin D, low 1,25D levels were associated with poor outcome. To date, a small observational study among KTRs 29 , as well as a propensity-matched study of CKD 30 , suggests that active vitamin D therapy improves renal outcomes. Future randomized interventional studies are therefore warranted to assess the effect of active vitamin D use on graft outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Its deficiency increases the vulnerability to infections, increases generalized inflammation, increases risks for diseases and infections, and worsens chronic diseases [ 12 , 39 , 40 ]. Consequently, hypovitaminosis increases the susceptibility to infections and diseases and enhances the severity of illnesses [ 41 ], leading to increased complications and premature deaths [ 42 , 43 , 44 ]. Vitamin D has pleiotropic effects on body systems, especially the immune, musculoskeletal, cardiovascular, pulmonary, neurological, gastrointestinal, and renal systems.…”
Section: Consequences Of Vitamin D Deficiencymentioning
confidence: 99%
“…The importance of the above is highlighted by six positive respiratory tract infection-related RCTs, most conducted in children [ 42 , 43 , 57 , 58 , 59 ]; all of these used daily doses of vitamin D [ 101 , 102 , 134 ]. Another meta-analysis of RCTs on vitamin D supplementation in respiratory tract infections reported that vitamin D is most effective as a treatment when administered in daily doses than intermittently [ 135 ].…”
Section: What Has Changed Over the Years Related To Vitamin D?mentioning
confidence: 99%
“…In humans, the treatment with calcitriol in CKD patients promotes beneficial effects on the kidneys unrelated to PTH and mineral metabolism, including activity of renin-angiotensin-aldosterone system suppression, reduction of proteinuria, reduction of podocyte loss associated with glomerular hypertrophy and antiproliferative and antifibrotic effects [114][115][116][117]. These effects seem to be important to explain the benefits demonstrated by calcitriol therapy in CKD human patients, where it has been shown to limit the progression of CKD, improve survival and be independently associated with preservation of renal function [116,118].…”
Section: Effects Of Vitamin D On the Parathyroid Glandmentioning
confidence: 99%